PENERAPAN NILAI-NILAI LOKAL KEPEMIMPINAN KEPALA SMA NEGERI DI KABUPATEN WAJO (Studi Kasus Pada Kepala SMA Negeri 1 Pammana) - Wardah, Andi (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2017)
The Implementation of local Values in the Principal’s Leadership of Public Senior High School in Wajo District. The application is an implementation of leadership behavior of principals through actions demonstrated as the education managers. Those actions are applied through various behaviors of local values in facing various demand and situational constraints in the process. This research applied qualitative approach in a form of descriptive method. The results of the research revealed that: the value of siri’ or ashame, reso’ or effort, lempu’ or honesty, getteng‘ or constancy, were the local values applied by the principal that (i) the local value named as siri’ was applied and given to the teachers, staff, students, committee, parents, and community by the principal, which was not only limited by giving DP3, but also in many aspects regarding the aspects in the school, (ii) the Buginese value named as reso’  or the effort conducted maximally by the principal by empowering all the member of the school. The empowerment was conducted by impvolving all personnels in planning, active in the application, and transparency in evaluation, (iii) the value of lempu’ was the basic fundamental in establishing relationship among humans and one of basic factors in life, and (iv) the value of getteng’ had been conducted maximally to involve teachers, students, parents, and community in the principal’s leadership.